Condition monitoring of power module using S-parameters, TDR, and TDT. (November 2022) - Pascal, Y.; Daschner, F.; Liserre, M.; Höft, M.
Abstract: Condition monitoring of power electronics is gaining interest as power electronics expends to mission-critical applications. This paper offers a preliminary experimental study of the viability of using S-parameters and time-domain reflectometry measurements to monitor the degradation of a power module. To this end, measurements were performed on a standard high current power module which was artificially aged by cutting wire bonds one by one. The study demonstrates a clear trend in the evolution of measured parameters, and thereby the possibility to monitor the power module degradation under the specific test conditions. This opens a new condition monitoring technology for power electronics systems. Highlights: RF technologies are used for State of Health assessment. Power electronics ageing is detected using S-parameters and TDR. S-parameters are used for condition monitoring of power electronics.